Drawing masterclass life drawing - Armer, Eddie (Tunbridge Wells search press, 2015)
Eddie Armer shows how to approach life drawing in pencil, charcoal, ballpoint pen or wax crayon, using a variety of techniques
13
Keywords: Figure drawing -- Technique; Human figure in art